Great Soul of Siberia : passion, obsession, and one man's quest for the world's most elusive tiger - Park, Sooyong Cineasta (Greystone Books, 2015)
In The Great Soul of Siberia, renowned tiger researcher Sooyong Park tracks three generations of Siberian tigers living in remote southeastern Russia. Reminiscent of the way Timothy Treadwell (the so-called Grizzly Man) immersed himself in the lives of bears, Park sets up underground bunkers to observe the tigers, living thrillingly close to these beautiful but dangerous apex predators. At the same time, he draws from twenty years of experience and research to focus on the Siberian tigers' losing battle against poaching and diminishing habitat. Over the two years of his harrowing stakeout, Park's poignant and poetic observations of the tigers draw a fiercely compassionate portrait of these elusive, endangered creatures.tomade de:https://www.bookdepository.com/Great-Soul-Siberia-Sooyong-Park/9781771641135